1997
DOI: 10.1029/97jb01645
|View full text |Cite
|
Sign up to set email alerts
|

A new analysis of the great 1970 Colombia earthquake and its isotropic component

Abstract: Abstract.Several methods of low-frequency analysis are used to determine the source mechanism of the July 31, 1970, Great Colombia earthquake and to reexamine two controversial results previously obtained for this event. In a classic study of the earthquake, Dziewonski and Gilbert [1974] concluded (1) that low-frequency (f < 4 mHz) mode spectrum observations require an isotropic compression at the source of a magnitude similar to the deviatoric moment release and (2) that the isotropic component of moment rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Some early studies explored the possibility that implosive phase change of mantle materials could cause intraslab earthquakes (e.g., Leith and Sharpe, 1936). However, subsequent studies have revealed that both intermediatedepth and deep-focus earthquakes generally do not have the large isotropic components that would be expected if this mechanism occurred (e.g., Hara et al 1996;Kawakatsu, 1991Kawakatsu, , 1996Kuge and Kawakatsu, 1993;Okal, 1996;Russakoff et al 1997;Estabrook, 1999). Therefore, some other mechanism must exist to generate intraslab events.…”
Section: Introductionmentioning
confidence: 95%
“…Some early studies explored the possibility that implosive phase change of mantle materials could cause intraslab earthquakes (e.g., Leith and Sharpe, 1936). However, subsequent studies have revealed that both intermediatedepth and deep-focus earthquakes generally do not have the large isotropic components that would be expected if this mechanism occurred (e.g., Hara et al 1996;Kawakatsu, 1991Kawakatsu, , 1996Kuge and Kawakatsu, 1993;Okal, 1996;Russakoff et al 1997;Estabrook, 1999). Therefore, some other mechanism must exist to generate intraslab events.…”
Section: Introductionmentioning
confidence: 95%
“…Careful reanalysis of low-frequency spectra of the great 1970 Columbia earthquake indicates no significant isotropic component (Dziewonski and Gilbert, 1974;Russakoff et al, 1997). Similarly, a very broadband analysis of the 1994 Bolivia earthquake limited an isotropic component to < 1-2% (Hara et al, 1995).…”
Section: Nature Of the Seismic Sourcementioning
confidence: 99%
“…While a brittle failure model is well suited to explain rupture occurring at low lithospheric pressures (e.g., crustal earthquakes), this mechanism should be prohibited for generation of deep earthquakes, as pressures and temperatures at tens of kilometers are large enough to inhibit brittle failure, and allow for ductile flow instead. However, deep earthquakes have similar mechanism solution to those of their shallow counterparts [ Russakoff et al ., ], both representing predominantly shear slip. On the other hand, deep seismicity has features that are significantly different from those of crustal earthquakes.…”
Section: Introductionmentioning
confidence: 99%